Synthesis of superfine high-entropy metal diboride powders. (1st July 2019) - Liu, Da; Wen, Tongqi; Ye, Beilin; Chu, Yanhui
Abstract: High-purity and superfine high-entropy metal diboride powders, namely (Hf0.2 Zr0.2 Ta0.2 Nb0.2 Ti0.2 )B2, were successfully synthesized via a facile borothermal reduction method at 1973 K for the first time. The as-synthesized powders with an average particle size of 310 nm had a single-crystalline hexagonal structure of metal diborides and simultaneously possessed high compositional uniformity from nanoscale to microscale. In addition, their formation mechanisms were well interpreted by analyzing the thermodynamics of the possible chemical reactions based on the first-principles calculations. This work will open up a new research field on the synthesis of high-entropy metal diboride powders. Graphical abstract: High-purity and superfine high-entropy metal diboride powders with a single-crystalline hexagonal structure and high compositional uniformity, namely (Hf0.2 Zr0.2 Ta0.2 Nb0.2 Ti0.2 )B2, were successfully synthesized via a facile borothermal reduction method at 1973 K for the first time.Unlabelled Image